Pengenalan Teknologi Informasi (TI) dan Pelatihan Penggunaan Microsoft Office bagi Masyarakat Desa Topanda Kabupaten Bulukumba - Nur, Muhammad Awal; Farida, Farida; Sulaiman, Husni (Empowerment, 2021)
This community service activity in the form of Introduction to Information Technology (IT) and Microsoft office training aims (1) to provide an understanding of the Topanda Village community about the introduction of information technology, (2) To train the Topanda Village community in using Microsoft office (Excel, Powerpoint and Word). This activity was carried out in Topanda Village, Rilau Ale Subdistrict, Bulukumba Regency on 29-30 May 2021 which was attended by village officials, PKK members and Topanda Village youth groups. The method used in this service activity is training and lectures on the introduction of information technology. The activity began with an explanation of the material then continued with a demonstration exercise on how to operate Microsoft office. The results of this service activity are (1) increasing the understanding of the Topanda Village community regarding Information Technology and providing the ability for the Topanda Village community to operate Microsoft Office especially Excel, Powerpoint and Word programs, (2) assisting village officials in operating computerized data and speeding up the process. administration of the Topanda Village community. The community and government officials of Topanda Village, Rilau Ale District, Kab. Bulukumba was very enthusiastic about participating in this training. AbstrakKegiatan pengabdian kepada masyarakat berupa Pengenalan Teknologi Informasi (TI) dan Pelatihan Microsoft office ini bertujuan (1) untuk memberikan pemahaman masyarakat Desa Topanda tentang pengenalan teknologi informasi, (2) Melatih masyarakat Desa Topanda dalam menggunakan Microsoft office (Excel, Powerpoint dan Word). Kegiatan ini dilaksanakan di Desa Topanda Kecamatan Rilau Ale Kabupaten Bulukumba pada tanggal 29 – 30 Mei 2021 yang diikuti aparat desa, anggota PKK dan karang taruna Desa Topanda. Metode yang digunakan dalam kegiatan pengabdian ini adalah pelatihan dan ceramah mengenai pengenalan teknologi informasi. Kegiatan dimulai dengan penjelasan materi kemudian dilanjutkan dengan latihan demonstrasi cara mengoperasikan Microsoft office. Hasil kegiatan pengabdian ini adalah (1) meningkatkan pemahaman masyarakat Desa Topanda mengenai Teknologi Informasi serta memberikan kemampuan bagi masyarakat Desa Topanda dalam mengoperasikan Microsoft Office Khususnya program Excel, Powerpoint dan Word, (2) membantu aparat desa dalam mengoperasikan data secara komputerisasi dan mempercepat dalam proses pengurusan administrasi masyarakat Desa Topanda. Masyarakat dan aparat pemerintahan Desa Topanda Kecamatan Rilau Ale Kab. Bulukumba sangat antusias mengikuti pelatihan ini.